Implementation Of The Complete Systematic Land Registration (Ptsl) Program In The Bengkulu City Land Office Area In 2023 - Caroline, Nia; Lorita , Evi; Handayani , Tuti (Multidisciplinary Journals, 2024)
The purpose of this study was to determine the description of the Implementation of the Complete Systematic Land Registration (PTSL) Program in the Bengkulu City Land Office area in 2023. The research method used is Descriptive qualitative method and data collection techniques through observation, interviews and documentation, the technique of determining informants in this study is using purposive sampling method where the number of informants is 4 people. In this analysis method using the Edward III (1984) theoretical approach which includes 4 indicators of implementation policy, namely Communication, Resources, Disposition, Bureaucratic Structure. The results of the research on the implementation of the PTSL program in communication with the community regarding the PTSL program at the Land Office of Bengkulu City in 2023 are the coordination process that has been socialized through counseling and social media well, the resources are all sufficient and adequate, both financially and the achievement of targets and facilities are fulfilled and the budget for the PTSL program in 2023 is sufficient, disposition in the PTSL program implementation policy at the Land Office of Bengkulu City in 2023, has been running well in accordance with legal norms and has transparency in the administrative process, according to their functions and duties at the Land Office of Bengkulu City. The bureaucratic structure in the PTSL program implementation policy at the Land Office of Bengkulu City in 2023 is in accordance with the standard operating procedure (SOP).